A framework for educating and empowering students by teaching about history and consequences of bias in STEM. Issue 1 (7th April 2022) - Moreau, Corrie S; Darby, Andrea M; Demery, Amelia-Juliette C; Arcila Hernández, Lina M; Meaders, Clara L
Abstract: Racism and bias are pervasive in society—and science, technology, engineering, and mathematics (STEM) fields are not immune to these issues. It is imperative that we educate ourselves and our students about the history and consequences of this bias in STEM, investigate the research showing bias toward marginalized groups, understand how to interpret misuses of science in perpetuating bias, and identify advances and solutions to overcome racism and bias throughout our professional and personal lives. Here, we present one model for teaching a universal course for participants of all professional stages to address these issues and initiate solutions. As very few institutions require students to enroll in courses on racism and bias in STEM or even offer such courses, our curriculum could be used as a blueprint for implementation across institutions. Ultimately, institutions and academic disciplines can incorporate this important material with more region and/or discipline specific studies of bias. Abstract : The authors present one model for teaching a universal course for participants of all professional stages to address racism, bias, and exclusion in STEM, and discuss the literature around these issues and why it is important to teach courses like these.